Creativity of biotechnological immunology: invention, naturalness and being - Pirc, Tadej (Creativity Studies, 2016)
The article discusses three intertwined issues posed by the modern biotechnological immunology and its creativity potential: invention, naturalness and Being. In the first part, the author reflects on evolutionary paradigm and Peter Sloterdijk’s theory of immunology, particularly in their relation to the biotechnological enhancement of human beings. The second part discusses Being’s own naturalness and the possibility of creative invention. In the third part, the author combines these viewpoints to highlight some metaphysical challenges of biotechnological immunology. Most importantly the forgotten question of what does it mean to be, especially after the postmetaphysical annulment of the possibility of death. The core thesis argues for the naturalness of the creative biotechnological practice for preventive and reparative purposes.First published online: 11 Apr 2016